The Role of Subcultures in Defining Urban Identities - Rahmat Hidayat; Luis Santos; Maria Clara Reyes (Yayasan Adra Karima Hubbi, 2024)
identities is often overlooked in urban studies, which place more emphasis on mainstream culture. Purpose. This study aims to identify and analyze how subcultures affect urban identity, especially in the context of social interaction and public policy in the city of Padang. Method. The research uses a qualitative approach with case studies, involving in-depth interviews and participatory observations. Results. The results show that subcultures have a significant influence in shaping urban identity through cultural expression, social participation, and more inclusive urban policies. Subcultures not only enrich the visual and aesthetic dimensions of cities, but they also play an important role in creating more welcoming and participatory public spaces. Conclusion. This study concludes that subcultures can be a strategic component in more sustainable and adaptive urban planning, albeit with limitations in scope and research methods that need to be further developed.